Transient anabolic effects of synovium in early post-traumatic osteoarthritis: a novel ex vivo joint tissue co-culture system for investigating synovium-chondrocyte interactions. Issue 7 (July 2021) - Lai-Zhao, Y.; Pitchers, K.K.; Appleton, C.T.
Summary: Objective: Osteoarthritis (OA) is a serious joint disease with no disease-modifying medical treatment. To develop treatments targeting synovium, we must improve our understanding of the effects of OA-related changes in synovial physiology on joint tissue outcomes. The aim of this study was to investigate the effects of synovial pathology due to post-traumatic OA (PTOA) on articular chondrocyte physiology. Methods: We first developed and validated a novel joint tissue co-culture system to model the biological interactions between synovium and articular chondrocytes. Whole-joint synovial tissue from a surgical rat model of PTOA vs sham and surgical-naïve controls was placed into a co-culture system with adult primary articular chondrocytes ( n = 4–5). The effects of PTOA synovium on chondrocyte anabolic, inflammatory, and catabolic gene expression and sulfated glycosaminoglycan (sGAG) secretion and aggrecan synthesis were tested, and results from early and later stages of PTOA development were compared. Results: Synovial injury by arthrotomy (sham surgery) alone decreased primary chondrocyte expression of genes including Col2a1 (0.36 ± 0.15-fold) and Acan (0.41 ± 0.28-fold). Early PTOA synovium rescued the suppression of Acan, induced increased sGAG secretion (3.94 ± 0.44 μg/mL vs surgery-naïve 2.41 ± 0.55 and sham 2.92 ± 0.73 μg/mL controls), and upregulated Mmp3 (3.73 ± 2.62-fold) and Prg4 (4.93 ± 4.29-fold). These effects were lost with later stage PTOA synovium. Conclusions: Early PTOA synovium induces transient anabolic responses in articular chondrocytes rather than pro-inflammatory responses that would require inhibition. These results suggest that PTOA synovium plays at least a partially protective role and that loss of these protective effects may contribute to PTOA progression.